1991
DOI: 10.1007/bf01296806
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of endoscopic sphincter of Oddi manometry

Abstract: Results from endoscopic sphincter of Oddi manometry are being used to support the diagnosis of sphincter dysfunction in patients with unexplained pain after cholecystectomy. However, there are few data on the reproducibility of manometric records or motility diagnosis during a second test. In this study, the reproducibility of manometric records was assessed in 12 patients with pain after cholecystectomy by performing a second study after three months. Manometric tracings were evaluated without access to patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(23 citation statements)
references
References 9 publications
0
22
0
1
Order By: Relevance
“…This finding is consistent with 2 other studies in the last decade which involved both sphincters, but contrasts with the almost 100% reproducibility in earlier studies looking only at the biliary sphincter (Table). 1,[7][8][9][10] Significant lack of reproducibility is not surprising, since the measurements span only a few minutes and sphincter pressures are known to vary with the migratory motor complex. 11,12 Furthermore, there may be subtle differences in medication use in sedation/anesthesia, confounding the interpretation of sphincter measurements, as opiates are known to cause sphincter of Oddi spasm.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with 2 other studies in the last decade which involved both sphincters, but contrasts with the almost 100% reproducibility in earlier studies looking only at the biliary sphincter (Table). 1,[7][8][9][10] Significant lack of reproducibility is not surprising, since the measurements span only a few minutes and sphincter pressures are known to vary with the migratory motor complex. 11,12 Furthermore, there may be subtle differences in medication use in sedation/anesthesia, confounding the interpretation of sphincter measurements, as opiates are known to cause sphincter of Oddi spasm.…”
Section: Discussionmentioning
confidence: 99%
“…With current techniques, SOM is performed over relatively short periods of time, whether manometric finding s can be considered representative of overall sphincter function is now being questioned [26]. Prolonged transductal manometry detects short periods of either rapid phasic contractions or absence of phasic activity that are rarely seen during short ERCP recordings [1].…”
Section: Reproducibility Of Manometry Findingsmentioning
confidence: 99%
“…Validation studies of SOM have shown that interobserver error can be relevant in the absence of a standardized approach to interpretation of manometric recordings. However, observer errors become negligible when interpretation is done by experts or when interpretation follows an agreed-upon, standardized approach [26,27].…”
Section: Normal Sphincter Of Oddi Manometric Valuesmentioning
confidence: 99%
“…To facilitate anatomic orientation, contrast can be injected into the biliary or pancreatic system prior to manometry without affecting the basal SO pressure [31•]. If SO manometry is done by experienced investigators, the results are fairly stable and reproducible [32]. The major clinical drawback of SO manometry is the relatively high risk of iatrogenic pancreatitis.…”
Section: Problems Of So Manometrymentioning
confidence: 99%